2016
DOI: 10.5455/ijmsph.2016.26102015182
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of transfusion-transmitted infections (TTIs) in blood donors: a study from central India

Abstract: Background: Transmission of infectious diseases such as HIV, hepatitis, syphilis, and others through donated blood needs a serious monitoring to provide safe blood for transfusion, which forms an integral part of medical and surgical therapy. Objective: To access the seroprevalence of transfusion-transmitted infections (TTIs) in Malwa region and assess the level of blood safety. Material and Methods: A prospective observational study was conducted for the duration of 12 months. The known seropositive donors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 15 publications
7
18
1
Order By: Relevance
“…Out of 2015 donations, males contributed to a larger percentage (96.5%) compared to females (3.5%), which is in concordance with the data given by a similar other study. [3] Syphilis (1.2%) was the most common TTI in the present study, which is in contrast to the data of other studies [1][2][3][4][5][10][11][12][13] where HBV was the most common TTI, and where as in the study by Kaur H et al [14] HCV was most the common TTI. None of the donor in our study was positive for HCV, but all other studies noted HCV prevalence of which Kaur H et al [14] had reported the highest HCV prevalence (1.79%).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Out of 2015 donations, males contributed to a larger percentage (96.5%) compared to females (3.5%), which is in concordance with the data given by a similar other study. [3] Syphilis (1.2%) was the most common TTI in the present study, which is in contrast to the data of other studies [1][2][3][4][5][10][11][12][13] where HBV was the most common TTI, and where as in the study by Kaur H et al [14] HCV was most the common TTI. None of the donor in our study was positive for HCV, but all other studies noted HCV prevalence of which Kaur H et al [14] had reported the highest HCV prevalence (1.79%).…”
Section: Discussioncontrasting
confidence: 99%
“…[1] In the present study, out of total donors, replacement donors constituted 68.7% and voluntary donors constituted 31.3%. Similar predominance of replacement donors was noted in other studies [3][4][5][6][7][8] while on the contrary, Sunderan S et al [1] , Bhattacharya P et al [9] , Shah N et al [10] noted predominance of voluntary donors in their studies. Out of 2015 donations, males contributed to a larger percentage (96.5%) compared to females (3.5%), which is in concordance with the data given by a similar other study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…5 Various studies reported from different parts of India show that many blood banks still rely on Replacement type of donors to maintain adequate stock. 6,7,8,9 This points towards the fact, that in India, national blood policy is not uniformly implemented, since blood donation services are mainly hospital based and highly decentralized. We conducted this study, to find the prevalence of voluntary donors and replacement donors in our blood bank, to compare voluntary -replacement donors year wise and gender wise, and also to study the pattern of both, voluntary and replacement donors over the period of time.…”
Section: Replacement Blood Donormentioning
confidence: 99%